2023
DOI: 10.1021/acsami.3c09351
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Complementary Logic Circuit Enabled by Al2O3 Passivation-Induced Carrier Polarity Modulation in Tungsten Diselenide

Tanmoy Das,
Sukhyeong Youn,
Jae Eun Seo
et al.

Abstract: Achieving effective polarity control of n-and p-type transistors based on two-dimensional (2D) materials is a critical challenge in the process of integrating transition metal dichalcogenides (TMDC) into complementary metal-oxide semiconductor (CMOS) logic circuits. Herein, we utilized a proficient and nondestructive method of electron-charge transfer to achieve a complete carrier polarity conversion from p-to n-type by depositing a thin layer of aluminum oxide (Al 2 O 3 ) onto tungsten diselenide (WSe 2 ). By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…As an example, it is revealed that the SnSe field-effect transistor with an h-BN encapsulation layer exhibits substantially reduced hysteresis as compared to a bare SnSe device [123]. In addition, Das et al demonstrated that the mobility of an Al 2 O 3 -passivated WSe 2 field-effect transistor is ≈5.5 times that of a bare WSe 2 device [124].…”
Section: Interface Passivationmentioning
confidence: 99%
“…As an example, it is revealed that the SnSe field-effect transistor with an h-BN encapsulation layer exhibits substantially reduced hysteresis as compared to a bare SnSe device [123]. In addition, Das et al demonstrated that the mobility of an Al 2 O 3 -passivated WSe 2 field-effect transistor is ≈5.5 times that of a bare WSe 2 device [124].…”
Section: Interface Passivationmentioning
confidence: 99%
“…Various materials, oxide, gallium arsenide, perovskite, graphene, TMDs, porous crystalline, biological, and organic materials have been employed in the development of the high-performance neuromorphic devices [11][12][13][14][15]. Among them, perovskite and TMD materials have attract broad attention due to the diversity, high charge carrier mobility [16][17][18][19][20][21][22][23][24][25], and excellent optoelectronic characteristics [26][27][28][29][30][31][32]. Despite the exceptional stability, compact cell size, high integration density, flexible temperature sensitivity and remarkable stability exhibited by metal oxide-based neuromorphic devices [33][34][35][36][37][38], their functionality remains relatively subpar, particularly in terms of optoelectronic response properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ion-implantation, a processing widely used in silicon technology for precise doping, is of little use in doping ultrathin 2D semiconductors of layered transition metal dichalcogenides (TMDs), which has triggered noticeable research efforts towards alternative mechanisms. So far, various approaches such as chemical doping, 13 plasma doping, 14 metal contact doping 15–17 and spacer doping 18–20 have been explored to achieve different doping for lateral/vertical p–n homojunctions based on mechanically exfoliated WSe 2 or CVD-grown species.…”
Section: Introductionmentioning
confidence: 99%